Eosinophilic Meningitis due to Angiostrongylus cantonensis in Children - Phan, Hai Thanh (Case Rep Neurol, 2021)
Meningoencephalitis is not a rare disease in children. However, eosinophilic meningitis due to Angiostrongylus cantonensis is unusual in the pediatric population. We describe the case of a 12-year-old girl from the central area of Vietnam with eosinophilic meningitis due to A. cantonensis. The patient lived in a rural area, where farming is widespread, and presented with fever and headache. Laboratory results showed peripheral eosinophilia, a cerebrospinal fluid white blood cell count of 730/mm3 with 65% eosinophils. Cerebrospinal fluid ELISA was positive for A. cantonensis, and blood ELISA was positive for A. cantonensis. The presentation was consistent with a diagnosis of A. cantonensis eosinophilic meningitis. The patient recovered fully after administration of albendazole (200 mg/day for 2 weeks), as well as intravenous dexamethasone (0.6 mg/kg/day every 8 h) and mannitol (1.5 g/kg/day every 8 h) for the first 3 days, followed by 5 days of oral prednisolone (2 mg/kg/day).